2013
DOI: 10.5121/ijnlc.2013.2202
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Web Search Results for Effective Arabic Language Browsing

Abstract: ABSTRACT

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…Sahmoudi and Lachkar [ 36 ] found that it was impossible to apply the STC algorithm directly to the Arabic language because of its properties. Therefore, they integrated STC into a new scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Sahmoudi and Lachkar [ 36 ] found that it was impossible to apply the STC algorithm directly to the Arabic language because of its properties. Therefore, they integrated STC into a new scheme.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, in our case, to deal especially with Arabic snippets, we propose also in this step to remove Latin words and specials characters such as (e.g. $, #,...) [15].…”
Section: A Document's "Cleaning"mentioning
confidence: 99%